Penyelesaian Sengketa Kepemilikan Atas Tanah Antara Para Pemegang Hak - Faradhiba, Tahta; Subekti, Subekti (Syura: Journal of Law, 2023)
Various issues of land disputes in Indonesia often cause polemics that drag on in social life, moreover land is a natural resource that has high value. The Basic Agrarian Law is the basis for legal protection which also creates derivative regulations to resolve land cases. The information in the certificate of land rights must match the physical data and juridical data recorded in the measurement letter and the land book concerned. This clarity and consistency provides legal certainty and prevents ambiguity. In essence, the principles of justice and legal certainty are the main ones and must be given to the community, especially to the disputing parties. This study discusses efforts to resolve land ownership disputes. Using normative research methods, land dispute resolution begins with administrative procedures for government agencies, in this case by the National Land Agency, through mediation, to litigation by the General Court and the Arbitration Board. Keywords: Land Disputes, Rights Holders.